Is UV radiation changing the toxicity of compounds to zebrafish embryos - Almeida, Ana Rita; Andrade, Thayres S; Burkina, Viktoriia; Fedorova, Ganna; Loureiro, Susana; Soares, Amadeu M V M; Domingues, Inês (Ecotoxicology and environmental safety, 2015)
At ecosystems level, environmental parameters such as temperature, pH, dissolved oxygen concentration and intensity of UV radiation (UVR) have an important role on the efficiency of organisms' physiological and behavioral performances and consequently on the capacity of response to contaminants. Insignificant alterations of these parameters may compromise this response. In addition, these parameters can additionally alter chemical compounds by inducing their degradation, producing thereafter other metabolites. Understanding the combined effects of chemicals and environmental parameters is absolutely necessary for an adequate prediction of risk in aquatic environments. According to this scenario, this work aims at studying the combined toxicity of UVR and three xenobiotics: the biocide triclosan (TCS), the metal chromium (as potassium dichromate, PD) and the fungicide prochloraz (PCZ). To achieve this goal zebrafish (Danio rerio) embryos (3h post fertilization (hpf)) were exposed to several concentrations of each chemical combined with different UV intensities; mortality and eggs were recorded every 24h for the all test duration (96 h). Results showed different response patterns depending on the toxicant, stress levels and duration of exposure. The combination of UVR and TCS indicated a dose ratio deviation where synergism was observed when UVR was the dominant stressor (day 2). The combination of UVR and PD presented a dose level dependency at day 3 indicating antagonism at low stress levels, changing with time where at day 4, a dose ratio deviation showed statistically that synergism occurred at higher PD concentrations. Finally, UVR combined with PCZ indicated a dose ratio at day 3 and dose level deviation at day 4 of exposure, suggesting a synergistic response when PCZ is the dominant stressor in the combination. The obtained results in this study highlighted the importance of taking into account the possible interaction of stressors and time of exposure to better predict environmental risk.
Keywords: dvojchroman draselný; Water Pollutants, Chemical; Potassium Dichromate; Triclosan; zvířata; Anti-Infective Agents, Local; embryo nesavčí; průmyslové fungicidy; ultrafialové záření; Zebrafish; imidazoly; antiinfekční látky lokální; dánio pruhované; Embryo, Nonmammalian; Fungicides, Industrial; triclosan; Animals; Ultraviolet Rays; Imidazoles; chemické látky znečišťující vodu